Α-C–C agostic interactions and C–H bond activation in scandium cyclopropyl complexes. Issue 24 (17th November 2020) - Xu, Cheng; Li, Guangyu; Etienne, Michel; Leng, Xuebing; Chen, Yaofeng
Abstract : Electron deficient scandium cyclopropyl complexes have been synthesized and fully characterized for the first time, and a combination of solid XRD, solution NMR and theoretical studies well demonstrated the α-C–C agostic interactions in the complexes. Abstract : This paper addresses the problem of the observation of the so-called C–C agostic interactions in cyclopropyl complexes of scandium. Three new cyclopropyl complexes of scandium based on the β-diketiminato ligand were synthesized including by an intramolecular C–H bond activation reaction in one case. X-ray diffraction analysis revealed distorted cyclopropyl groups in the complexes, and the distortion could be observed in solution as well for one of the complexes thanks to the natural abundance INADEQUATE NMR spectroscopy which showed a markedly reduced J C–C coupling constant. This signature of the C–C agostic interaction was further examined using DFT modelling which, together with NBO calculations, indicated that C–H and C–C agostic interactions are not exclusive but can complement each other, accounting for the distortions. The intramolecular C–H bond activation in the scandium biscyclopropyl complex was investigated by isotopic labeling experiments, which indicated a direct proton abstraction of the isopropyl group in the β-diketiminato ligand by a cyclopropyl group.